Taxonomic circumscription of Adenomera martinezi (Bokermann, 1956) (Anura: Leptodactylidae: Leptodactylinae) with the recognition of a new cryptic taxon through a bioacoustic approach - de Carvalho, Thiago Ribeiro; Giaretta, Ariovaldo Antonio (Zootaxa, 2013)
In this paper, we provide a taxonomic circumscription of Adenomera martinezi from its type locality (Cachimbo, southwestern State of Pará) since its description (57 years ago) based on a newly collected series of eleven adult topotypes, and through a bioacoustic approach, recognize an undescribed cryptic taxon under this nominal species, which is widely distributed in central and northern Brazil. Adenomera martinezi and Adenomera saci sp. nov. can be diagnosed from all congeners by their distinctive 4–6 symmetrically arranged rows of longitudinal dark-colored spots on dorsum. They differ from each other through advertisement call structure, pulsed in Adenomera martinezi (audibly pulsed to the human ear), and non-pulsed in Adenomera saci sp. nov. (a whistle to the human ear). The recognition of Adenomera saci sp. nov. has conservation implications. Based on our assumed distribution of A. martinezi and Adenomera saci sp. nov., the IUCN conservation status of A. martinezi requires a reassessment, inasmuch as we herein reconsider this species, as far as we know, as endemic to Cachimbo, southwestern State of Pará, Brazil. The 2004 extinction risk assessment included both A. martinezi and Adenomera saci sp. nov., and the conservation status category of ‘Least Concern’ might only be applied to Adenomera saci sp. nov., a widely distributed and abundant species in central and northern Brazil.